Sosialisasi Pedoman Gizi Seimbang "Isi Piringku" di Desa Pakuan, Kecamatan Narmada, Kabupaten Lombok Barat - Bachmida, Elya Antariksana; Afni, Nur; Widyastuti, Sri; Alamsyah, Ahmad; Handayani, Baiq Rien; Handito, Dody; Ariyana, Mutia Devi; Cicilia, Siska; Amaro, Moegiratul; Rahayu, Tri Isti; Sinaga, Yesica Marcelina Romauli; Pawestri, Setyaning; Perdhana, Firman Fajar (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Nutritional issues within the Indonesian society continue to be a major concern for the  government, as they significantly affect public health and the development of human resources in the long term. West Nusa Tenggara is one of the provinces with a malnutrition rate of 5.75% among children in 2022. Pakuan Village is a tourist village in West Lombok Regency, where most of the residents are farmers with abundant natural resources. "Isi Piringku" is a healthy eating guideline that emphasizes balanced nutrition by considering portion sizes and food variety, including staple foods, animal protein, plant-based protein, vegetables, and fruits. The programme  aims to educate the community in Pakuan Village about the importance of consuming balanced and nutritious meals by developing "Isi Piringku" menus as an effort to prevent nutritional problems in the village. The program consisted of preparation, implementation, and evaluation stages, It was conducted on August 15, 2024, from 09:30 to 11:30 WITA, at the Pakuan Village, Narmada Sub-district, West Lombok Regency. The event was attended by 20 participants, the majority of whom were women and members of the local Kelompok Sadar Wisata (Pokdarwis). Participants were highly enthusiastic and responded positively to this initiative. The results of this activity indicate that participants were highly enthusiasm throughout the session and demonstrated an improved knowledge, as observed throughtheir ability to answer the feedback questions given.. This programme successfully increased the awareness of the people of Pakuan Village regarding the importance of balanced nutrition and how to create an "Isi Piringku" menu. It is hoped that this programme can be carried out sustainably with support from the government and local healthcare professionals to promote a healthy lifestyle within the community.ABSTRAKPermasalahan gizi yang terjadi di tengah masyarakat Indonesia masih menjadi perhatian pemerintah mengingat dampaknya yang luas terhadap kesehatan dan kualitas sumber daya manusia di masa depan. Nusa Tenggara Barat menjadi salah satu provinsi dengan anak penderita gizi buruk sebesar 5,75% di tahun 2022. Desa Pakuan merupakan salah satu desa wisata di Kabupaten Lombok Barat dimana sebagian besar penduduknya merupakan petani dengan hasil alam yang melimpah. Isi Piringku adalah salah satu pedoman makan sehat yang menekankan pemenuhan gizi seimbang dengan memperhatikan porsi dan variasi makanan, termasuk makanan pokok, lauk hewani, lauk nabati, sayuran, dan buah-buahan. Tujuan dari kegiatan pengabdian ini adalah meningkatkan pengetahuan dan kesadaran masyarakat di Desa Pakuan tentang pentingnya penerapan pedoman gizi seimbang dengan menyusun menu “Isi piringku” sebagai salah satu upaya untuk mencegah terjadinya masalah gizi di masyarakat desa. Kegiatan pengabdian terdiri dari tahap persiapan, pelaksanaan dan evaluasi, dilakukan pada tanggal 15 Agustus 2024 pukul 09.30-11.30 WITA di Aula Balai Desa Pakuan Kecamatan Narmada Kabupaten Lombok Barat. Kegiatan ini diikuti oleh 20 peserta mayoritas perempuan melibatkan anggota Kelompok Sadar Wisata (Pokdarwis) Desa Pakuan. Hasil dari kegiatan ini adalah peserta sangat antusias   selama kegiatan dan menunjukkan peningkatan pengetahuan yang dinilai melalui observasi  dimana peserta mampu menjawab pertanyaan umpan balik yang diberikan. Kegiatan pengabdian ini berhasil meningkatkan pemahaman masyarakat Desa Pakuan tentang pentingnya gizi seimbang dan bagaimana menyusun menu “isi piringku”. Diharapkan program ini dapat dilakukan secara berkelanjutan dengan dukungan dari pemerintah dan tenaga kesehatan setempat untuk menciptakan pola hidup sehat di masyarakat.